Tradisi Biantara dan Paparikan dalam Pembuka Tata Ibadat Pemberkatan Pertunangan Masyarakat Sunda-Katolik - Riyanto, Thomas Galih Joko (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2022)
Language is an inseparable element of culture and is capable of expressing complex realities. The universal Church and the local churches are connected in the process of inculturation of faith, where pastoral workers should pay attention to the local socio-cultural conditions. Inculturation is not only considered in rituals, but also has an impact on the moral-ethical dimension of the faithful. The principles of lex orandi and lex credendi can be complemented by the principle of lex agendi, where the spreading of the Gospel not only teaches truths but also introduces culturally relevant elements in the process of inculturation. Inculturation in the Sundanese culture as the context of this article requires wise steps and in-depth study to understand the backgrounds and the theological perspective of the local culture. This article analyzes the role of Biantara and Paparikan of the Sundanese culture in the ritual of engagement in the Catholic Church as well as in the preparatory exercises. This practice of inculturation needs to be evaluated in order to reconsider the viewpoints of the faithful, the need for further development, and the possible modifications that might be required in the local church context.